Patients with Amyotrophic Lateral Sclerosis Have High Interest in and Limited Access to Genetic Testing. Issue 3 (20th October 2016) - Wagner, Karin N.; Nagaraja, Haikady; Allain, Dawn C.; Quick, Adam; Kolb, Stephen; Roggenbuck, Jennifer
Abstract: Although genetic testing for amyotrophic lateral sclerosis (ALS) is widely available, it is unknown what proportion of patients with ALS have access to genetic counseling and testing, and patient attitudes towards ALS genetic testing have not been studied. We conducted a national survey of ALS patients enrolled in the Agency for Toxic Substances and Disease Registry, which consisted of multiple choice questions and two 12 item Likert scale series assessing respondents' experience with and attitude toward genetic testing. The survey had an 8 % response rate, with 449 completed responses. Genetic testing was offered to 33.4 % and completed by 67.1 % of those offered. A minority of respondents (12.5 %) saw a genetic counselor, and were much more likely to be offered genetic testing ( p  = 0.0001). Respondents with a family history of ALS (8.4 %) were more likely to be offered testing ( p  = 0.0001) and complete testing ( p  = 0.05). Respondents with a family history of ALS were more likely to report a favorable attitude towards genetic testing ( p  = 0.0003), as were respondents who saw a genetic counselor ( p  = 0.02). The majority of respondents (82.7 %) felt that genetic testing should be offered to all patients with ALS. Our results indicate that ALS patients may have limited access to genetic testing, but perceive benefit from this service. Development of practice guidelines for genetic testing in ALS, to include the routine offer of genetic counseling, may result in broader and more consistent access to these services.